Body Mass Index and Nationality (Argentine vs. Spanish) Moderate the Relationship Between Internalization of the Thin Ideal and Body Dissatisfaction: A Conditional Mediation Model - Moreno-Domínguez, Silvia; Rutsztein, Guillermina; Geist, Thomas A.; Pomichter, Emily E.; Cepeda-Benito, Antonio (Frontiers in Psychology, 2019)
It is believed that Women’s exposure to Western sociocultural pressures to attain a “thin-ideal” results in the internalization of a desire to be thin that consequently leads to body dissatisfaction (BD). It is also well documented that body mass index (BMI; kg/m2) correlates with BD. We tested for the first time a conditional mediation model where thin-ideal Awareness predicted BD through Internalization of the thin ideal and the path from Internalization to BD was hypothesized to be moderated by BMI and Nationality (Argentine vs Spanish). The model was tested with a sample of 499 young women (age = 18 to 29) from Argentina (n = 290) and Spain (n = 209). Awareness and internalization were measured with the SATAQ-4 (Schaefer et al., 2015) and BD was measured with the BSQ (Cooper et al., 1987). The model was analyzed using PROCESS v3.1 (Hayes, 2018). As hypothesized, thin-ideal awareness predicted BD through internalization and the path from internalization to BD was moderated by BMI and nationality. Specifically, internalization predicted BD at all level of BMI and in both samples, but the relationship between internalization and BD increased with BMI and was also stronger among Spaniards than Argentines. We argue that the findings congruent with theories that predict that economic development and modernization contribute to normative female BD through internalization of the thin ideal and that upward social comparisons or cognitive discrepancy between self-perceived body image and the sociocultural thin ideal interacts synergistically with thin-ideal internalization to increase BD.